Digestibility Values of Feed Available in Bangkalan Regency For Beef Cattle - Kusmartono; Mashudi; Poespitasari Hazanah Ndaru; Aprilia Dwi Kartika; Trio Angger Saputro (Jurnal Nutrisi Ternak Tropis, 2023)
A great attention to improve Madura cattle has been given by government of East Java, especially the one related to nutrition, reproduction and health. This study only focussed on evaluating digestibility values of feeds currently available in Bangkalan regency using an in vitro approach.  A purposive sampling involving 40 farmers was done for two weeks to obtain information of feeds offered, and samples of the feed were taken to the laboratory for nutrients content and digestibility evaluation. Six feed treatments were applied, included A1-A3 rations practised by farmers for cows (A1), bulls (A2) and crossbred Limousin (A3), and B1-B3 formulated rations using local materials taken from the Bangkalan farmers for cows (B1), bulls (B2) and crossbred Limousin (B3). Rumen fluid samples were collected from abattoir at three different collection times for in vitro evaluation.